Peran Saturasi Oksigen Serebral yang Diukur Menggunakan Near-Infrared Spectroscopy (NIRS) dalam Mengevaluasi Luaran Resusitasi pada Anak dengan Renjatan - Irene Yuniar; Arifah Nur Shadrina (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2021)
Shock in children remains public health importance and causes significant morbidity and mortality worldwide. Hypoperfusion in shock results in decreased oxygen delivery to the tissues, causing a shift from more efficient aerobic pathways to anaerobic metabolism, which results in lactate as the end product. Unlike blood lactate measurement, near-infrared spectroscopy (NIRS) monitoring system is safe and easy to use in measuring tissue oxygenation non-invasively. However, NIRS monitoring has yet to be validated against a standard measure of regional oxygenation. The primary objective of this article is to review the role of cerebral oxygen saturation (rSO2) measured by NIRS in evaluating the outcome of pediatric shock resuscitation.